Effect of daily chlorhexidine bathing on reducing infections caused by multidrug‐resistant organisms in intensive care unit patients: A semiexperimental study with parallel controls. Issue 1 (13th February 2023) - Huang, Wenzhi; Qiao, Fu; Cai, Lin; Zong, Zhiyong; Zhang, Wei
Abstract: Objective: To assess the effectiveness of daily bathing by chlorhexidine bathing on multidrug‐resistant organisms in ICU, especially on carbapenem‐resistant Acinetobacter baumannii (CRAB), carbapenem‐resistant Pseudomonas aeruginosa (CRPA), and carbapenem‐resistant Enterobacteriaceae (CRE). Methods: Semiexperimental study which employed both precontrols and a parallel control was conducted. In the intervention period (from July 1 to December 31, 2016), strengthened infection control measures and daily bathing with 2% CHG‐impregnated wipes once daily was performed in the ICU. Fifty‐seven non‐ICU wards with the occurrence of multidrug‐resistant organisms (MDRO) infections during the same time were selected as parallel control group (only CHG bathing was not performed). The net effect of the 2% CHG daily bathing was evaluated by the difference in difference (DID) model. Results: The DID model analysis showed that CHG bathing reduced the incidence of CRAB‐ and CRPA‐caused infections in ICU by 1.56 and 2.15 cases/1000 patient days, and bathing of every 19 patients (95CI% 13 to 41) and 39 patients (95CI% 24 to 110) were able to prevent one case of HAIs of total MDROs and CRPA, respectively. However, CHG bathing showed no effect on MRSA, VRE, and CRE ( p  > 0.05). Conclusion: Daily bathing with 2% CHG‐impregnated wipes can reduce HAIs caused by CRAB and CRPA, while it is not effective for the prevalence of infections caused by MRSA, VRE, and CRE.